School stress and health complaints: Testing the Adolescent Stress Questionnaire in Spain and Sweden. (20th October 2021) - García-Moya, I; Corell, M; Paniagua, C; Vaez, M; Löfstedt, P
Abstract: Background: According to the Health Behaviour in School-aged Children (HBSC) study, over a third of adolescents feel pressured by schoolwork in European countries, with increases associated to age and in girls. School pressure has been linked with increased health complaints, which illustrates the importance of schools from a public health perspective. To get a better understanding of school stress in adolescence, there is a need to test measures that reflect a broader array of potential school-related stressors. The aims of this cross-national study were: (1) to analyze the functioning of a specific measure to assess school stress in adolescence and (2) to examine the links between school stress and health complaints. Methods: The sample consisted of students aged 13 and 15 years: 1, 249 students (54.6% girls) who had participated in project EASE in Spain, and 576 students (50.6% girls) in Sweden. The measure tested was the Adolescent Stress Questionnaire (ASQ-S), specifically the 9 items on school stress from the subscales school performance, future uncertainty, and school-leisure conflict. For the assessment of health complaints, the HBSC health complaints checklist was used. Results: CFA supported a three-correlated factor structure and a high reliability of the three subscales of the ASQ-S in both countries. In regression analyses, the association between school stress and health complaints was significant when controlling age and sex, with the increase in the level of explained variability due to several stress dimensions being 18.8% in Spain and 25.2% in Sweden. Conclusions: Different facets of school life can contribute to stress during adolescence, with more public health attention needed when it comes to school stress and its links with increased health complaints. Key messages: The instrument used for school stress may be useful in cross-national studies in adolescent samples. More public health attention should be paid to school stress and its links with increased health complaints in adolescence.